Effects of glutamine and serum on IGF- dependent cho-K1 cell growth in T-Flask - Mohamed, Vasila Packeer; Hashim, Yumi Zuhanis Has-Yun; Mohmad Saberi, Salfarin Ezrina; Ibrahim, Siti Nuramalis; Amid, Azura; Mel, Maizirwan (American-Eurasian Network for Scientific Information, 2014)
An effective mammalian cell culture based host system is highly desirable for production of bio-therapeutics. There are several strategies to achieve an effective system, one of which is regulation of media coupled with exploitation of inherent characteristics of cell line. In this present study, it is hypothesized that glutamine and serum may affect CHO-K1 cell growth through Insulin-like Growth Factor-I (IGF-I)pathway. The effects of glutamine and serum on IGF-dependent CHO-K1 cell growth in T-flask were studied based on three-level Full Factorial Design generated by SIMCAP+v12 (Umetrics, Sweden). The combination factor of 0.50 mM glutamine and 10 % (v/v) serum was found to be the optimal condition producing 8.87 x 105 cells/ml. The CHO-K1 culture was also found to be able to grow in zero glutamine reaching 16.60 x 105 cells/ ml. Meanwhile, improvement of cell growth can also be achieved in reduced serum level with the presence of IGF-I protein.